EFEKTIVITAS PENGGUNAAN GAME EDUKATIF BLOOKET DALAM MENINGKATKAN HASIL BELAJAR SISWA MANAJEMEN PERKANTORAN KELAS X DI SMK NEGERI 1 LAMONGAN - Makiyah Damayanti; Febrika Yogie Hermanto; Triesninda Pahlevi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effectiveness of the educational game Blooket in improving students’ learning outcomes in the subject Office Management Basics and Business Services for Grade X at SMK Negeri 1 Lamongan. The research employed a quasi-experimental method with a Pretest-Posttest Nonequivalent Control Group design involving two classes: an experimental group using Blooket and a control group receiving conventional instruction. Data were collected through pretests, posttests, and student questionnaires. The results of the N-Gain analysis and Independent Sample t-test showed a higher improvement in learning outcomes in the experimental group. Students also responded positively to Blooket, considering it engaging, easy to use, and motivating. Therefore, Blooket is effective in enhancing student engagement and learning achievement and is suitable as an alternative interactive learning medium in vocational schools.